Macroalgal community structure and beta diversity in the coastal waters of East Lombok, Indonesia - ABDULLAH RASYID; MASTERIA YUNOVILSA PUTRA; WINDRI HANDAYANI; YASMAN YASMAN (Society for Indonesian Biodiversity, 2025)
Abstract. Rasyid A, Putra MY, Handayani W, Yasman. 2025. Macroalgal community structure and beta diversity in the coastal waters of East Lombok, Indonesia. Biodiversitas 26: 3115-3124. Coastal ecosystems in East Lombok, Indonesia, are home to diverse macroalgal communities influenced by local environmental factors. This study investigates macroalgal community structure and beta diversity across three distinct locations: Station 1 (Dasan Ujung Beach), Station 2 (Telong Elong Beach), and Station 3 (Pinky Beach). The survey categorized macroalgae into Chlorophyta, Rhodophyta, and Phaeophyta, and employed Simpson and Sørensen dissimilarity indices alongside the nestedness-resultant component (?sne) to assess community variability. The results show that Station 2, with a complex substrate of coral rubble and calcareous mud, supported a more diverse macroalgal community, including calcifying species like Halimeda spp. In contrast, eutrophic conditions at Station 3 promoted the dominance of Ulva lactuca, a species indicative of nutrient-rich waters. The beta diversity indices reveal that substrate type and nutrient enrichment play critical roles in shaping macroalgal diversity and community composition, rather than water chemistry alone. These findings suggest that habitat heterogeneity and local anthropogenic pressures significantly influence coastal biodiversity. This study contributes new insights into the ecological drivers of macroalgal distribution in East Lombok and offers a framework for future marine conservation and monitoring.